2006
DOI: 10.1002/cvde.200506465
|View full text |Cite
|
Sign up to set email alerts
|

4H SiC Epitaxial Growth with Chlorine Addition

Abstract: The growth rate of a 4H-SiC epitaxial layer has been increased by a factor of 19 (up to 112 lm h -1 ) with respect to the standard process, with the introduction of HCl in the deposition chamber. The epitaxial layers grown with the addition of HCl has been characterized by electrical, optical, and structural characterization methods. The effects of various deposition parameters on the epitaxial growth process have been described, and an explanation of this behavior in terms of the diffusion coefficient on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…II B, new epitaxial processes that overcome some of these limitations have been developed 45,75 which represent, together with the step-controlled growth mode, a technological breakthrough in SiC epitaxies. In these new processes, the growth rate has been increased with respect to the standard ones by increasing the silane flow combined with the introduction of Chloride-based chemistry, either adding HCl 76 to the Silane precursor or substituting it with trichlorosilane (TCS).…”
Section: High Growth Rate Epitaxy Processmentioning
confidence: 99%
“…II B, new epitaxial processes that overcome some of these limitations have been developed 45,75 which represent, together with the step-controlled growth mode, a technological breakthrough in SiC epitaxies. In these new processes, the growth rate has been increased with respect to the standard ones by increasing the silane flow combined with the introduction of Chloride-based chemistry, either adding HCl 76 to the Silane precursor or substituting it with trichlorosilane (TCS).…”
Section: High Growth Rate Epitaxy Processmentioning
confidence: 99%
“…However, despite the importance of this topic, scarce experimental and theoretical information is present in the literature. La Via et al 1 have shown by deep level transient spectroscopy (DLTS) that both the Z 1=2 and EH 6=7 levels are present in n-type 4H-SiC grown by using HCl as a precursor and that new deep levels, related to Cl, are not observed, at least in the 10 13 cm À3 range. Subsequently, by employing density functional theory (DFT), it was found that Cl preferably occupies a C-site rather than a Si-site and behaves as a triple donor.…”
Section: Introductionmentioning
confidence: 99%
“…6). The effect of Cl/Si ratio on the morphology of the epitaxial layers 31 and on the growth rate 32,33 has been reported previously. A decrease in growth rate for lower Cl/Si ratio 33 due to insufficient formation of SiCl 2 and for higher Cl/Si ratio 32 due to etching of the growing epitaxial layers was found.…”
Section: à2mentioning
confidence: 99%